PENGGUNAAN MODEL PEMBELAJARAN MAKE A MATCH DALAM MENINGKATKAN KEMAMPUAN KOSAKATA BAHASA INGGRIS SISWA KELAS V SD NEGERI 2 MAPARAH - Purwanti, Siti Dewi; Hidayat, Yusuf; Khoer, Misbahul (Jurnal Intisabi, 2025)
English vocabulary ability is one of the important aspects in learning and understanding English effectively. This study aims at determining the use and impact of employing “Make a Match” learning model to improve the 5th grade students’ English vocabulary ability of SD Negeri 2 Maparah. This study uses a qualitative method under a classroom action research (CAR) approach. The results of the study show that the use of Make a Match learning model is proven to be significantly successful to improve the 5th grade students’ English vocabulary ability of SD Negeri 2 Maparah, as indicated by an increasing of the completion score of 62.5% in cycle I to 93.75% in cycle II. In addition, the use of Make a Match learning model shows a positive impact to improve the 5th grade students’ English vocabulary ability of SD Negeri 2 Maparah. In conclusion, the use of Make a Match learning model is effective to improve the 5th grade students’ English vocabulary ability of SD Negeri 2 Maparah.